Modification of Imperfect Cancer Drugs to Become Perfect Cancer Drugs to Save Cancer Patients - Liau, Ming C.; Craig, Christine L.; Baker, Linda L. (British Journal of Healthcare and Medical Research, 2024)
The objective of this study is to develop perfect cancer drugs to save cancer patients. A specific aim is to save King Charles who was recently diagnosed to have cancer. Perfect cancer drugs are the drugs capable of inactivating abnormal methylation enzymes (MEs) to take out both cancer stem cells (CSCs) and cancer cells (CCs) by inducing these cells to undergo terminal differentiation, and to restore chemo-surveillance to save cancer patients. Imperfect cancer drugs are cytotoxic agents capable of killing CCs but cannot affect CSCs, which also contribute to the destruction of chemo-surveillance to cause fatality of advanced cancer patients. The ineffectiveness against CSCs and the destruction of chemo-surveillance are responsible for the failure of imperfect cancer drugs to cure cancer. Cell differentiation agent-2 (CDA-2) was a persuasive perfect cancer drug approved by the Chinese FDA, the rest of the world do not have a really perfect cancer drug. CDA-2 was a preparation of wound healing metabolites purified from urine, which could serve as a model for the development of CDA formulations as perfect cancer drugs. Wound healing metabolites active as differentiation inducers (DIs) and differentiation helper inducers (DHIs) are the active players of chemo-surveillance created by the nature as allosteric regulators of abnormal methylation enzymes (MEs), which are the most critical issue of cancer. The elimination of abnormal MEs is very effective to cure cancer. Wound healing is a simple matter that comes naturally, because the nature creates chemo-surveillance to ensure perfection of wound healing. Cancer is the consequence of wound unhealing due to the collapse of chemo-surveillance. Cancer therapy can also be a simple matter, if the therapy follows wound healing process. PSCs and CSCs are cells with abnormal MEs, which are protected by drug resistance and anti-apoptosis mechanisms. PSCs are the cells involved in wound healing. Efficient induction of terminal differentiation of PSCs is very critical to the success of wound healing. Natural DIs and DHIs are the partners of PSCs and CSCs in wound healing, which can easily access to PSCs and CSCs. If wound is not healed, PSCs are forced to evolve into CSCs and then to progress to faster growing CCs. CCs display a high level of degradative enzymes to generate substrates for the syntheses of macromolecules to support their faster growth. Natural DIs and DHIs may be rapidly degraded in CCs. A different set of unnatural DIs and DHIs may be necessary to achieve the induction of terminal differentiation of CCs. Thus, two sets of CDA formulations, one CDA-CSC with natural DIs and DHIs, and another CDA-CC with non-natural DIs and DHIs to accomplish effective therapy of cancer. We have carried out extensive studies on natural DIs and DHIs presented in the urine, and unnatural DIs and DHIs as telomerase inhibitors, signal transduction inhibitors, targeted therapeutic agents and growth inhibitors for the formulations of CDA-CSCs and CDA-CCs.